2012
DOI: 10.1097/hjh.0b013e3283524910
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of central aortic systolic pressure using late systolic inflection of radial artery pulse and its application to vasodilator therapy

Abstract: Noninvasive cSBP calculated with rSBP2 accorded well with aSBP measured by the invasive method. Vasodilator medication and four of five diseases did not affect this relation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 24 publications
2
43
0
Order By: Relevance
“…The first and second systolic peaks were automatically identified using the fourth derivative wave as the second and third zero crossing points, respectively. Late systolic blood pressure (SBP) in the radial artery was used as an estimate of the central SBP; measurements of the central SBP estimated by the HEM-9000AI are very close to that determined following invasively recorded aortic central SBP [6]. Brachial blood pressure and heart rate were measured simultaneously in the right brachium with an oscillometric device incorporated in HEM-9000AI.…”
Section: Experimental Designmentioning
confidence: 98%
See 1 more Smart Citation
“…The first and second systolic peaks were automatically identified using the fourth derivative wave as the second and third zero crossing points, respectively. Late systolic blood pressure (SBP) in the radial artery was used as an estimate of the central SBP; measurements of the central SBP estimated by the HEM-9000AI are very close to that determined following invasively recorded aortic central SBP [6]. Brachial blood pressure and heart rate were measured simultaneously in the right brachium with an oscillometric device incorporated in HEM-9000AI.…”
Section: Experimental Designmentioning
confidence: 98%
“…been recently developed and is capable of estimating the central blood pressure from radial arterial waveforms, has been developed [5,6]. Previous studies have shown that central blood pressure is higher in obese individuals than in non-obese people [7].…”
mentioning
confidence: 99%
“…SBP2 has been shown to accurately reflect transfer functionderived aortic SBP and was used as central SBP substitute. 6,24,25 Echo-Doppler Examination of the Carotid Arteries Carotid arteries were evaluated using an SSD-3500SV (Aloka Co, Ltd, Tokyo, Japan) with a 7.5-MHz probe equipped with a continuous-flow Doppler and phase-locked echo-tracking system. Internal diameters of the common carotid artery at end-diastole (Dd) and peaksystole (Ds) were measured.…”
Section: Radial Waveform Analysis and Bp Measurementmentioning
confidence: 99%
“…Finally, an estimate of cSBP was calculated by the pressure at the late systolic shoulder of the radial pressure waveform using linear regression. 14,15 After an overnight fasting of at least 12 hours, a venous blood sample was obtained from the forearm of each participant. Serum or plasma samples were separated within 30 minutes of collection and were stored at −80°C, which were used for measurement of fasting blood glucose and the standard 75-g oral glucose tolerance test, total cholesterol, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol, triglycerides, and creatinine concentrations.…”
Section: Data Collectionmentioning
confidence: 99%